The trend of enteral feeding among critically- ill patients in adult ICUs in Malaysia - Japar, Salimah; Soh, Kim Lam; Che Hussin, Hatifah; Ibrahim, Nor Airini; Ong, Swee Leong; Soh, Kim Geok (GEOMATE International Society, 2017)
The adequacy of caloric intake is crucial for all critically-ill patients in Intensive Care Units because energy expenditure is higher in these patients compared to normal patients in general wards. Adequate calorie intake will promote positive outcome to the patients while inadequate calorie will lead to malnutrition which will increase the length of stay. The objective of this study was to determine the adequacy of caloric intake received by critically-ill patients in the general ICU in Malaysia. This was a cross sectional study which used a proforma adapted from ICU protocol. There were 132 participants involved in this study. The descriptive statistic and independent t-test were used for the statistical analysis. The results showed that 75.8% (n=100) received adequate or more than calorie prescribed while 24.2% (n=32) received calorie less than the given prescription. Patients that received early feeding were 72% (n=95) and late feeding were 28% (n=37). The continuous feeding method was most commonly used in early feeding patients from Day 1 to Day 3. There was an association between the adequacy of calorie intake and the length of stay (p<0.05). Findings obtained from this study will provide information for the nurses and other health care providers to improve the management of patients so that all patients will receive adequate caloric intake during their stay in ICUs.